Involvement of Norepinephrine in the Control of Activity and Attentive Processes in Animal Models of Attention Deficit Hyperactivity Disorder - D. Viggiano; L. A. Ruocco; S. Arcieri; A. G. Sadile (Neural Plasticity)
Functional and morphological studies in children affected by Attention Deficit Hyperactivity Disorder (ADHD) suggest a prefrontal cortex (PFc) dysfunction. This cortical region is regulated by subcortical systems including noradrenergic (NEergic), dopaminergic (DAergic), cholinergic, serotonergic, and histaminergic pathways. A wealth of data in humans and in animal models demonstrates altered dopamine (DA) regulation. Drugs that modulate norepinephrine (NE) transmission are also effective in ADHD patients, thus leading to the hypothesis of a NEergic disorder. This review covers the regulation of PFc functions by NE and the interaction between the NE and DA systems, as suggested by pharmacological, electrophysiological, morphological, and gene knock out (KO) studies. A negative feedback between NE and DA neurons emerges from KO studies because KO mice showing increased (NE transporter (NET) KO) or decreased (DBH and VMAT2 KO) NE levels are respectively associated with lower and higher DA levels. Locomotor activity can be generally predicted by the DA level, whereas sensitivity to amphetamines is by NE/DA balance. Some animal models of ADHD, such as spontaneously hypertensive rats (SHR), show alterations in the PFc and in the DA system. Evidence about a correlation between the NE system and hyper-locomotion activity in such animals has not yet been clarified. Therefore, this review also includes recent evidence on the behavioral effects of two NET blockers, reboxetine and atomoxetine, in two animal models of ADHD: SHR and Naples High Excitability rats. As these drugs modulate the DA level in the PFc, certain effects are likely to be due to a rebalanced DA system. We discuss the significance of the results for theories of ADHD and make suggestions for future experimentation.